Effect of semen dilution rate and dimethyl acetamide levels on post-thaw motility and fertility parameters of rooster sperm - Mohamed Shawky; Ahmed F. Fawy; Ahmed M. Elomda; Mohamed A. Elmenawey; Abd El-Rahman M. Atta; Ahmed O. Abbas; Gamal M. K. Mehaisen (PLoS ONE, 2025)
This study evaluated the impact of pre-freezing semen dilution rate and dimethyl acetamide (DMA) concentration on the post-thaw motility and fertility of cryopreserved rooster sperm. Rooster ejaculates were diluted with a standard EK extender to achieve low (LSC; 1 × 10⁹ sperm/mL) and high (HSC; 2 × 10⁹ sperm/mL) sperm concentrations. Each dilution group was further treated with three DMA concentrations (3%, 6%, or 9%) before cryopreservation. Post-thaw sperm motility traits were obtained by computer-assisted sperm analysis (CASA), and fertility features were evaluated through artificial insemination in hens. The current results showed that HSC significantly improved total motility (TM), curvilinear velocity (VCL), amplitude of lateral head displacement (ALH), and beat cross frequency (BCF), but reduced linearity (LIN) and straightness (STR) compared to LSC. DMA concentration had a quadratic effect on motility, with 6% yielding the highest progressive motility (PM), straight line velocity (VSL), and BCF. Fertility outcomes revealed that HSC resulted in higher fertilization rates, while neither DMA concentrations nor their interaction with dilution rates exerted significant effects on fertility traits. VCL, ALH, and BCF showed positive correlations with pipping-chicks rates, whereas STR, LIN, and WOB displayed negative correlations. These findings underscore the critical interplay between dilution rate and cryoprotectant concentration and provide practical guidance for developing more reliable cryopreservation protocols that can be applied under field conditions to enhance fertility management in poultry production.